The zero degree zombie zone - Bass, Patrik Henry (New York : Scholastic, 2014)
Fourth-grader Bakari Katari Johnson is having a really bad day--class bullies Tariq and Keisha are mad at him, his best friend Wardell has nominated him for hall monitor, a pack of ice zombies from a frozen world are demanding he return the magic ring that Keisha has, and somehow he has to find a way to save the school.
M
b
b
Keywords: Magic -- Juvenile fiction; Rings -- Juvenile fiction; Zombies -- Juvenile fiction; African American children -- Juvenile fiction; Best friends -- Juvenile fiction; Bullying -- Juvenile fiction; Elementary schools -- Juvenile fiction; Magic -- Fiction; Rings -- Fiction; Zombies -- Fiction; African Americans -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Bullies and bullying -- Fiction; Schools -- Fiction